Doxycycline, an Inhibitor of Mitochondrial Biogenesis, Effectively Reduces Cancer Stem Cells (CSCs) in Early Breast Cancer Patients: A Clinical Pilot Study - Scatena, Cristian; Roncella, Manuela; Di Paolo, Antonello; Aretini, Paolo; Menicagli, Michele; Fanelli, Giovanni; Marini, Carolina; Mazzanti, Chiara Maria; Ghilli, Matteo; Sotgia, Federica; Lisanti, Michael P.; Naccarato, Antonio Giuseppe (Frontiers in Oncology, 2018)
Background and objectives. Cancer stem cells (CSCs) have been implicated in tumor initiation, recurrence, metastatic spread and poor survival in multiple tumor types, breast cancers included. CSCs selectively overexpress key mitochondrial-related proteins and inhibition of mitochondrial function may represent a new potential approach for the eradication of CSCs. Because mitochondria evolved from bacteria, many classes of FDA-approved antibiotics, including doxycycline, actually target mitochondria. Our study aimed to determine whether short-term pre-operative treatment with oral doxycycline results in reduction of CSCs in early breast cancer patients. Methods. Doxycycline was administered orally for 14 days before surgery for a daily dose of 200 mg. Immuno-histochemical analysis of formalin-fixed paraffin-embedded (FFPE) samples from 15 patients, of which 9 were treated with doxycycline and 6 controls (no treatment), was performed with known biomarkers of “stemness” (CD44, ALDH1), mitochondrial mass (TOMM20), cell proliferation (Ki67, p27), apoptosis (cleaved caspase-3) and neo-angiogenesis (CD31). For each patient, the analysis was performed both on pre-operative specimens (core-biopsies) and surgical specimens. Changes from baseline to post-treatment were assessed with MedCalc 12 (unpaired t-test). Results. Post-doxycycline tumor samples demonstrated a statistically significant decrease in the stemness marker CD44 (p-value < 0.005), when compared to pre-doxycycline tumor samples. More specifically, CD44 levels were reduced between 17.65% and 66.67%, in 8 out of 9 patients treated with doxycycline. In contrast, only one patient showed a rise in CD44, by 15%. Overall, this represents a positive response rate of nearly 90%. Similar results were also obtained with ALDH1, another marker of stemness. In contrast, markers of mitochondrial mass, proliferation, apoptosis and neo-angiogenesis, were all similar between the two groups. Conclusions. Quantitative decreases in CD44 and ALDH1 expression are consistent with pre-clinical experiments and suggest that doxycycline can selectively eradicate CSCs in breast cancer patients in vivo. Future studies (with larger numbers of patients) will be conducted to validate these promising pilot studies.